2020
DOI: 10.1111/dmcn.14712
|View full text |Cite
|
Sign up to set email alerts
|

Hospital resource use after hip reconstruction surgery in children with neurological complex chronic conditions

Abstract: To assess how co-occurring conditions influence recovery after hip reconstruction surgery in children with neurological complex chronic conditions (CCCs). METHOD This was a retrospective analysis of 4058 children age 4 years or older with neurological CCCs who underwent hip reconstructive surgery between 1st January 2015 and 31st December 2018 in 49 children's hospitals. The presence of co-occurring chronic conditions was assessed using the Agency for Healthcare Research Chronic Condition Indicator system. Mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“… 6 Multisystem involvement and multiple comorbidities from a characteristic pattern of co‐occurring conditions are common, requiring an increased complexity of care. 7 , 8 , 9 , 10 , 11 …”
mentioning
confidence: 99%
“… 6 Multisystem involvement and multiple comorbidities from a characteristic pattern of co‐occurring conditions are common, requiring an increased complexity of care. 7 , 8 , 9 , 10 , 11 …”
mentioning
confidence: 99%
“…3 Neuromuscular hip dysplasia is common in nonambulatory children with neurological CCC and is often treated with surgical hip reconstruction. 8,9 Orthopaedic surgeries to treat children with neurologic CCC are high-cost procedures associated with increased complication rates, lengthy recovery times, and frequent hospital readmissions. 7,[10][11][12] Orthopaedic surgeries for musculoskeletal disease have been identified as the most common surgical cause of hospitalization for patients with neurologic CCC of all Gross Motor Function Classification System (GMFCS) levels with orthopaedic procedures involving the hip, lower extremity, or spine among the most frequent surgeries performed.…”
Section: Introductionmentioning
confidence: 99%
“…Children with neurologic CCC encompass static, progressive, central and peripheral neurological diseases, including, but not limited to cerebral palsy (CP), leukodystrophy, congenital brain malformations, muscular dystrophy, and spinal muscular atrophy 3. Neuromuscular hip dysplasia is common in nonambulatory children with neurological CCC and is often treated with surgical hip reconstruction 8,9. Orthopaedic surgeries to treat children with neurologic CCC are high-cost procedures associated with increased complication rates, lengthy recovery times, and frequent hospital readmissions 7,10–12.…”
Section: Introductionmentioning
confidence: 99%
“…There are two new reports on the surgical care of children with disabilities, using big data from administrative databases in Taiwan and the United States. 1,2 In the study by Huang et al, children with intellectual disabilities were found to have approximately double the odds of postoperative pneumonia, sepsis, and mortality. 1 Interestingly, the odds of adverse events were increased in both tertiary and non-tertiary settings.…”
mentioning
confidence: 99%
“…The risk of complications in children with disabilities increases with additional medical complexity. Berry et al used administrative data from 49 children’s hospitals in the United States to better understand the use of inpatient resources in children with neurological complex chronic conditions who underwent reconstructive hip surgery 2 . They showed that as the number of co‐existing conditions increased from one to four or more, length of stay increased by 67%, costs by 41%, and readmissions by 240%.…”
mentioning
confidence: 99%